Increased Risk for Dementia in Patients With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis of Population-Based Studies - Liu, Mengsi; Li, Dongxiu; Hong, Xia; Sun, Zhen (Frontiers in Neurology, 2022)
Background Mounting evidence suggests that there may be a causal relationship or common pathogenic pathway between inflammatory bowel disease (IBD) and dementia. However, inconsistent results have emerged from epidemiological studies. We therefore conducted this review to clarify the relationship between IBD and dementia. Methods We systematically searched PubMed, Web of Science, Embase, and Cochrane library to identify all studies exploring the relationship between IBD and dementia published as of September 2021. Risk estimates were pooled using both fixed and random-effects models. Results Six studies involving 2,334,472 subjects were included. Pooled results suggested that the risk of developing dementia significantly increased after IBD diagnosis (HR = 1.27, 95% CI: 1.10–1.47, P = 0.001), which did not vary by age, gender, dementia subtype, or IBD subtype. Whereas, the dementia incidence before IBD diagnosis and the comorbidity rate of dementia in IBD patients were similar to those without IBD (HR = 0.92, 95% CI: 0.68–1.25; 0.82, 95% CI: 0.64–1.06, respectively). However, current evidence was insufficient to establish a causal relationship. Conclusion This study shows an unidirectional association between IBD and dementia; patients with IBD have an increased risk of dementia, and it may be beneficial to develop individualized dementia screening strategies for this population. Future research needs to further investigate whether effective therapies of IBD can reduce this risk and pathophysiological mechanisms of the association.